Spatioselective Growth of Metal‐Organic Framework Nanocrystals on Compositionally Anisotropic Polymer Particles. (14th February 2014) - Park, Tae‐Hong; Lee, Kyung Jin; Hwang, Sangyeul; Yoon, Jaewon; Woell, Christof; Lahann, Joerg
<x xml:space="preserve">Abstract</x> Selective growth of metal organic framework materials on the surface of compartmentalized polymer microparticles is achieved by electro‐hydrodynamic co‐jetting, selective surface modification, and anisotropic crystal growth. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>